Study on the microstructure and properties of bromobutyl rubber (BIIR)/polyamide‐12 (PA12) thermoplastic vulcanizates (TPVs). Issue 8 (30th October 2015) - Ning, Nanying; Hu, Linjia; Yao, Pengjun; Wu, Hanguang; Han, Jibin; Zhang, Liqun; Tian, Hongchi; Tian, Ming
ABSTRACT: In this study, polyamide‐12 (PA12)/brominated isobutylene‐isoprene (BIIR) TPVs with good mechanical properties and low gas permeability were prepared by dynamic vulcanization in a twin‐screw extruder. The effects of three kinds of compatibilizers on the microstructure and properties of BIIR/PA12 TPV were studied. The compatibility between BIIR and PA12 was improved when maleated hydrocarbon polymeric compatibilizer is added. The reaction between maleic anhydride and amine in polyamide leads to the in situ formation of hydrocarbon polymer grafted polyamide which subsequently can be used to lower the interfacial tension between BIIR and polyamide. The compatibilizing effect of maleic anhydride modified polypropylene (PP‐ g ‐MAH) on BIIR/PA12 blends is the best among these compatibilizers because the surface energy of PP‐ g ‐MAH is very close to that of BIIR. The dispersed rubber phase of the blend compatibilized by PP‐ g ‐MAH shows the smallest size and more uniform size distribution, and the resulting TPVs show the best mechanical properties. The effects of fillers on the properties of BIIR/PA12 TPV were also investigated. The size of the BIIR phase increases with the increase in the content of CaCO3 . The modulus and tensile strength of TPVs increased with the increase in the content of CaCO3 because of the reinforcing effect of CaCO3 on TPVs. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43043. Abstract :